Albert Shaw of the Review of Reviews - Graybar, Lloyd J. (Lloyd Joseph), 1937-2000 (Book collections on Project MUSE., 1974)
The life of Albert Shaw (1857-1947) reflected in microcosm the changes that American society was undergoing through a critical period. This first full-length study focuses on two themes: Shaw's career as editor and publisher of the Review of Reviews, an influential monthly journal in the early years of the twentieth century, and Shaw's career as a public figure. Shaw was a member of the Progressive movement from its inception, but his concern and interests were wide-ranging, centering to a large degree on the question of what the industrialization of America meant. Lloyd J. Graybar shows incis.